Students’ Satisfaction With Online Learning During Covid 19 Pandemic At Ninth Grade Of MTS. TI Canduang - Para Dila Sandi; Eliza (CV. Ulil Albab Corp, 2022)
The purpose of this research was to find out the level of students’ satisfaction with online learning during COVID 19 pandemic at ninth grade of MT.s TI Canduang. The design of this research was descriptive quantitative research by using survey method. The instrument of this research was questionnaire to find out students’ satisfaction with online learning during COVID 19 pandemic. In this research, the population was all of the ninth grade students of MT.s TI Canduang which consisted of 5 classes. The sample was 36 students taken by simple random sampling. The instrument was validated by three experts. The data were processed by identifying the responses, counting the percentages of each indicator and taking the conclusion. The results of the research showed that the mean score on reliability was 64,01% which was on the level satisfied. The mean score on the tangible was 62,34% which was on the level satisfied. The mean score on the responsiveness was 64,56% which was on the level satisfied. The mean score on the assurance was 65,69% which was on the level satisfied. The mean score on the empathy was 65,14% which was on the level satisfied. So, the average mean of students’ satisfaction in online learning during COVID 19 pandemic was 64,35% which was on the level satisfied based on the interpretation table 61%-80%. So, it can be concluded that the student at ninth grade of MT.s TI Canduang felt satisfied with the online learning during COVID 19 pandemic.